A nanostructured paper-based device for phenylalanine neonatal screening by LED-induced fluorescence. Issue 12 (11th March 2020) - Moreira, Cristian M.; Marín-Barroso, Evelyn; Pereira, Sirley V.; Raba, Julio; Messina, Germán A.; Bertolino, Franco A.
Abstract : In this work, a novel paper-based analytical device (PAD) coupled with LED-induced fluorescence (LIF) detection (fPAD) for the rapid, selective, and sensitive quantification of phenylalanine (Phe) in neonatal samples was developed. Abstract : In this work, a novel paper-based analytical device (PAD) coupled to LED-induced fluorescence (LIF) detection (fPAD) for the rapid, selective, and sensitive quantification of phenylalanine (Phe) in neonatal samples was developed. The enzymes phenylalanine dehydrogenase (PheDH) and diaphorase were immobilized on a paper microzone previously modified with zinc oxide nanoparticles (ZnONPs) coated with chitosan (CH-ZnONPs). Phe was extracted from the blood spots collected from samples on a filter paper and was mixed with nicotinamide adenine dinucleotide (NAD + ) and resazurin. Then the mixture was deposited on the reaction microzone of the fPAD where PheDH converts Phe and NAD + to phenylpyruvate and NADH, respectively. Finally, NADH was oxidized by diaphorase with the consequent reduction of resazurin to resorufin. The latter was detected by LIF using an excitation wavelength of 535 nm and an emission wavelength of 580 nm using a synchronized video microscope. We compared the responses of the PADs with and without nanomaterials to demonstrate the improved analytical performance of the developed devices. For this, the PADs were modified with the same concentration of horseradish peroxidase (HRP). The fluorescent signal obtained from the PADs with nanomaterials was higher than that of the unmodified PADs. Our method exhibited within- and between-assay variation coefficients below 5.23% and 6.67%, respectively. The detection limit obtained by the developed device was 0.125 μM. The proposed fPAD allowed the simple, rapid, low-cost, and sensitive detection of Phe in neonatal blood samples.